2017
DOI: 10.1017/jfm.2017.625
|View full text |Cite
|
Sign up to set email alerts
|

Statistics of turbulence in the energy-containing range of Taylor–Couette compared to canonical wall-bounded flows

Abstract: Considering structure functions of the streamwise velocity component in a framework akin to the extended self-similarity hypothesis (ESS), de Silva et al. (J. Fluid Mech., vol. 823,2017, pp. 498-510) observed that remarkably the large-scale (energy-containing range) statistics in canonical wall bounded flows exhibit universal behaviour. In the present study, we extend this universality, which was seen to encompass also flows at moderate Reynolds number, to Taylor-Couette flow. In doing so, we find that also … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
28
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(35 citation statements)
references
References 53 publications
(85 reference statements)
7
28
0
Order By: Relevance
“…Even though the RB structure functions exhibit log-linear scaling for r/z 1 when plotted against separation distance, the slopes remain small at low Ra and they were found to vary significantly with both Ra and z + , rendering the analysis inconclusive in this point. While a dependence of the slopes on Re τ and wall-normal position is also observed for velocity structure functions (see Krug et al 2017), typically the log-linear scaling is much less evident in these cases compared to figure 2 at z + 100. Also for the scalar in channel flow investigated here (plots not shown) a direct scaling regime is not discernible such that it appears likely that the more prominent log-linear regimes in figure 2 are a consequence of the 2D setup.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…Even though the RB structure functions exhibit log-linear scaling for r/z 1 when plotted against separation distance, the slopes remain small at low Ra and they were found to vary significantly with both Ra and z + , rendering the analysis inconclusive in this point. While a dependence of the slopes on Re τ and wall-normal position is also observed for velocity structure functions (see Krug et al 2017), typically the log-linear scaling is much less evident in these cases compared to figure 2 at z + 100. Also for the scalar in channel flow investigated here (plots not shown) a direct scaling regime is not discernible such that it appears likely that the more prominent log-linear regimes in figure 2 are a consequence of the 2D setup.…”
Section: Discussionmentioning
confidence: 64%
“…The ESS framework has been demonstrated to extend the scaling regime not only to low Re but also to a wider range of wall-normal distances. In particular, Krug et al (2017) found convincing scaling for D u p /D u 1 as low as z + = 30. From figure 4a-c, it is clear that the same does not hold for the scalar structure functions in RB convection.…”
Section: Scalar Ess Scaling In Rb Convectionmentioning
confidence: 83%
See 2 more Smart Citations
“…For example, del Alamo et al [20] found evidence of wall-scaling in two-dimensional spectra for all three velocity components. Furthermore, Krug et al [21] showed universality across a wide range of flows for the streamwise and spanwise velocities using an extended form (i.e. the ratio between two structure functions of different orders).…”
Section: Introductionmentioning
confidence: 99%